#TITLE_ALTERNATIVE# - SASTROWIJOYO (NIM: 13204002), FAJAR
Implementation of space vector modulation for high power and medium voltage inverter using simple 8-bit microcontroller is proposed in this final project. The implementation process begins by selecting the suitable device that suits the needs of the implementation. The modulator is designed to facilitate vector control mode, Volts/Hertz mode and discontinued mode. Analysis of the results of the experiments is conducted by comparing output current waveforms, output current spectrums, ripple analysis, efficiencies and THDs from some experiments. Results obtained leads to conclusions about the accuracy of the implementation using this approach, maximum modulation parameter and readiness for further development.